Drought alters the biogeochemistry of boreal stream networks - Lluís Gómez-Gener (Nature Portfolio, 2020)
High latitude droughts are increasing, but their effects on freshwater systems are poorly understood. Here the authors investigate Sweden’s most severe drought in the last century and show that these dry conditions induce hypoxia and elevated methane production from streams.